2016
DOI: 10.1364/ol.41.005499
|View full text |Cite
|
Sign up to set email alerts
|

Axial super-resolution evanescent wave tomography

Abstract: Optical tomographic reconstruction of a 3D nanoscale specimen is hindered by the axial diffraction limit, which is 2-3 times worse than the focal plane resolution. We propose and experimentally demonstrate an axial super-resolution evanescent wave tomography (AxSET) method that enables the use of regular evanescent wave microscopes like Total Internal Reflection Fluorescence Microscope (TIRF) beyond surface imaging, and achieve tomographic reconstruction with axial superresolution. Our proposed method based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…As a clear demonstration of imaging performance for our Moirémetalens-based microscope, both standard resolution target and fluorescent microspheres are imaged, with a lateral resolution of ∼2 μm, as well as optical sectioning capability of ∼7 μm. The varifocal Moirémetalens with ultrathin size and compact design may replace its counterpart in any optical system that requires a focus-tunable lens, such as optical coherence tomography 50 and microendoscopy 19 for in vivo imaging.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…As a clear demonstration of imaging performance for our Moirémetalens-based microscope, both standard resolution target and fluorescent microspheres are imaged, with a lateral resolution of ∼2 μm, as well as optical sectioning capability of ∼7 μm. The varifocal Moirémetalens with ultrathin size and compact design may replace its counterpart in any optical system that requires a focus-tunable lens, such as optical coherence tomography 50 and microendoscopy 19 for in vivo imaging.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…However, it allows only one-dimensional magnification and is further limited when the host index is not small due to the loss of negative spatial frequencies. In many ways this is not entirely surprising, as dielectric prisms are known as dispersive tools for exciting surface plasmons [20] or for frustrated total internal reflection tomography [37], more so than they are for imaging. Here we explore whether hyperprism applications mimicking a conventional prism, tunably coupling free-space plane waves to high-k modes, are more promising.…”
Section: Applications Of High-k Mode Excitationmentioning
confidence: 99%
“…The sample is thus illuminated by only the evanescent field, which can allow for high longitudinal resolution. By scanning the angle of incidence and thus the penetration depth, a three-dimensional image with subwavelength longitudinal resolution can be reconstructed [37,44]. Total internal reflection microscopy is particularly useful to image within highly absorbing samples, for example, in water at THz frequencies [45].…”
Section: B Total Internal Reflection Microscopy and Tomographymentioning
confidence: 99%
“…On the other hand, fluorescence microscopy techniques such as wide-field microscopy, confocal microscopy and most of super-resolution (SR) microscopy exhibited axial resolution inferior to the lateral axis. By rapidly switching among multiple incident angles of the TIRF illumination (MA-TIRF), it has been shown that an axial resolution of ~50 nm is possible in live cells [1,2]. However, given that raw images are always convolution of fluorescence emission image with the point spread function (PSF) of the microscopy, the lateral resolution in previous studies did not reach the diffraction limit yet, as neither method deblurred the raw image with a deconvolution step.…”
Section: Introductionmentioning
confidence: 99%